Acquisition Practice in Nepalese Banking and its Financial Impact on Acquiring Bank - Rashesh Vaidya; Dhan Raj Chalise (Journal of Business and Social Sciences, 2022)
An acquisition is a strategic tool to enhance a competitive advantage. However, the acquisition practice in the Nepalese banking industry is done to strengthen the capital base of the acquiring bank and reduce the number of banks and financial institutions in the industry. The paper considers the commercial banks that have exercised acquisitions of other financial institutions since the enactment of the Acquisition Bylaws in 2013. Nepal Rastra Bank, has enacted acts and bylaws related to the acquisition of financial institutions. After the enactment of the Acquisition Bylaws in 2013, the number of development banks and finance companies heavily declined in the Nepalese financial market, as did the number of commercial banks, which also dropped through acquisitions and mergers between commercial banks. The results found that acquisition practices strengthen the capital base and manage the liquidity position of the acquiring commercial banks. Nevertheless, the acquiring bank needs to manage the non-performing loan, integrate human resources and accounting systems, and ultimately satisfy the shareholders of the acquired banks and financial institutions, as well as its own human resources and shareholders.